Basic characteristics of interior and embedded permanent magnet for double stator generator - Ibrahim, Nur Amira; Misron, Norhisam; Vaithilingam, Chockalingam Aravind; Aris, Ishak; Mailah, Nashiren Farzilah (Taylor's University, 2023)
The permanent magnet synchronous machines can be used for different applications depending on their structures and geometries proposed. It can convert the mechanical energy from the shaft into electrical energy by supplying current to it. Since the surface-mounted permanent magnet produces a high Eddy current, the Embedded and interior permanent magnet is proposed. This type of permanent magnet can prevent the permanent magnet from damage during the assembly and fabrication process. The double stator generator is proposed because it is capable to produce twice the power output compared to the conventional generator. This paper discusses the performance of the interior and embedded permanent magnet double stator generator (IEDSPG). The IEDSPG was designed and fabricated. Several tests have been done in this study to study the performance of IEDSPG including open circuit tests, frequency characteristics, and power characteristics for three different coil connections including inner-coil, outer-coil, and series-coil. When comparing coil connection conditions, the inner coil connection has the lowest resistance and inductance values. The IEDSPG was tested for 200 rpm as it is the required speed for the wind turbine system. Based on the testing, it can be concluded that an independent coil connection shows the best performance which produces up to 14 of generated power compared to the combined or series connection.